Prekmursko besedje za gospodarska poslopja, kmečko dvorišče in kmečka opravila v Pleteršnikovem slovarju - Koletnik, Mihaela (Slavia Centralis, 2020)
DIALECTAL PREKMURJE LEXEMES FOR FARM BUILDINGS, FARMYARDS, AND FARM CHORES IN PLETERŠNIK’S DICTIONARY This article presents lexemes denoting farm buildings, farmyards, and farm chores in the Prekmurje dialect to the extent specifed in the questionnaire used for the Slovenian Linguistic Atlas (SLA). Forty-seven replies to 56 questions were collected in three local dialects included in the SLA network of towns: Cankova (SLA 387), Večeslavci (SLA 397), and Grad (SLA 398). Documentation and semantics of the dialectal vocabulary were checked in Murko’s dictionary (1833), Pleteršnik’s dictionary (1894/95), in the Dictionary of Standard Slovene as well as in three more dictionaries that include the Prekmurje dialect vocabulary.